Ekonomi Digital dan Kebijakan Lokal: Strategi untuk Pembangunan Desa di masa Pandemi COVID-19 - Elia Nababan, Febrina; Karinawati Imron, Dian (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2022)
The development of digital villages today has been limited to providing administrative services and has not been used to develop the village economy and community welfare. The occurrence of COVID-19 pandemic has increased the challenges for village digital development. In spite of the difficulty, the digital economy through local policy contributes an opportunity to encourage rural economic resilience. This study aims to develop strategies of a digital economy for rural villages in the midst of a pandemic. The research is a case study located in Punggul Village, Badung, Bali Province. This research was conducted using qualitative research methods with data collection techniques using Focus Group Discussion and interviews. The result shows digital economic strategy could be implemented through several aspects including improving digital infrastructure facilities, enhancing the digital ecosystem, and identifying the potential and village featured products. Furthermore, cooperation between stakeholders needs to be strengthened in line with the local values.